Ultrasound guided rhomboid intercostal block provides effective pain control after video-assisted thoracoscopic surgery: A brief report of three cases - Çiftçi, Bahadır; Ekinci, Mürsel; Atalay, Yunus Oktay (Korean Society of Anesthesiologists, 2021)
Dear editor;Rhomboid intercostal block (RIB) is a novel block and it may be used for several indications[1,2]. It may be performed for open thoracotomy [3], however more information is needed for otherthoracic procedures. Video-assisted thoracic surgery (VATS) has the advantages of reduced painover open thoracotomy. However patients may still feel moderate to severe pain after VATS [4].Herein, we report RIB in 3 patients for analgesia management after VATS. Written informedconsent for the procedure and future publishing were obtained from the patients.
Keywords: Thoracoscopic Surgery; Pain Control; Intercostal Block